Ultra-high temperature metamorphism in the Lewisian Complex, South Harris, NW Scotland - Baba, Sotaro (1998)
P(論文) Two types of sapphirine-bearing granulites have been found in South Harris, NW Scotland. Both indicate ultra-high temperature conditions (over 900℃). Sapphirine-bearing orthopyroxene-sillimanite granulite contains orthopyroxene+sillimanite+sapphirine+garnet±cordierite as the pre-stable assemblage, indicating P-T conditions of 930-980℃ and 8-9 kbar. The other type, sapphirine-bearing orthopyroxene-kyanite granulite, contains two types of orthopyroxene (porphyroblast and intergrowth with kyanite), and sapphirine inclusions within aluminosilicate (mainly sillimanite). The orthopyroxene porphyroblasts have Al_2O_3 up to 9.7 wt%, indicating P-T condition of 1000-1050℃ and 10-11 kbar, while orthopyroxene intergrown with kyanite only have Al_2O_3 up to 7.5 wt%, indicating P-T conditions of 900℃ and 12-14 kbar. The inferred P-T path, mainly based on the orthopyroxene-kyanite granulite, had an anticlockwise trajectory with sapphirine+quartz breaking down to produce sillimanite+orthopyroxene intergrowths, followed by the aluminosilicate transition from sillimanite to kyanite. This is the first record of such ultra-high temperature metamorphism in South Harris. The UHT metamorphism may be a significantly distinctive thermal event that will prove important in reconstruction of the evolutional history of the Lewisian Complex at Palaeoproterozoic period. departmental bulletin paper